Progress in 'taxonomic sufficiency' in aquatic biological investigations. (December 2022) - Chen, Xuechao; Han, Meiaoxue; Liang, Yantao; Zhao, Wanting; Wu, Yuejiao; Sun, Ying; Shao, Hongbing; McMinn, Andrew; Zhu, Liyan; Wang, Min
Abstract: The 'taxonomic sufficiency' (TS) approach has been applied to algae, protists, invertebrates, and vertebrates, generally by aggregating species-level abundance data to a higher taxonomic level, where genus-level data are often highly correlated with species-level data and are a valid proxy level. The TS approach offers the possibility of a comparison of data from different geographical areas and highlights the effects of contaminants. The TS approach is stable in the face of different researchers and in the comparison of long-term biological survey data. The effectiveness of the TS approach may increase with increasing environmental gradients or spatial area. The TS approach should be avoided when the spatial area is small and small differences in species-level data are considered important, so as not to cancel out the distribution patterns specific to the local environment of the biological taxa. Highlights: 'Taxonomic sufficiency' approach has been applied to a wide range of biological taxa. Genus-level data is a valid proxy level. The TS approach is stable across researchers and long-term biological survey data. Larger environmental gradients or larger spatial areas suits the TS approach.